LANGUAGE AND PRINCIPLE OF HOPE - Lobanov, S.D. (Perm Federal Research Centre Journal, 2016)
In the article the problems of language and hope through the prism of modernity are considered. It is shown that the principle of hope has several manifistations, as well as its language.